CARNAVALIZAÇÃO E COMPLEXIDADE TURÍSTICA: FORMAÇÃO DE PAISAGENS RITUAIS EM EVENTOS NO ESTADO DO CEARÁ - OLIVEIRA, Christian Dennys (UFPR, 2008)
The study of the formation of new metropolitan shrines, in the Brazilian religious culture, has aroused interesting discussions in contemporary geography. A focus exploited little about is the need to transform the expressions of faith in shows, for the cautious and visitors. In this work, the investigation of this trend is in the observation of processes that make these rituals spectacular events. Whether in the construction of an aesthetic that imitate the greatness of the Brazilian carnival, whether in the service to the demands of this emerging tourist imitation. Reflecting on the mechanisms that “carnavalização”, the study tracks firstly the festivities of the patron saints and popular in the city of Fortaleza in major cities in the interior of the state of Ceará. In a second part, it made the approach about the tourist aspects involving the growth of these events. This shows the complex game of interests in the exploitation of urban spaces occupied by these events and the importance of interpreting the representation of this cultural practice tourism with innovative theoretical tools.